ByzRev 08.2026.014: James Howard-Johnston, Byzantium in a Changing World.: Oxford: Oxford University Press 2025. - Boutziopoulos, Gavriil-Ioannis (The Byzantine Review, 2026)
James Howard-Johnston, Byzantium in a Changing World. Oxford: Oxford University Press 2025. 280 pp. – ISBN 978-0-19-889789-7